2018
DOI: 10.1001/jamacardio.2018.1533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Density Lipoprotein Cholesterol Assessment by Martin/Hopkins Estimation, Friedewald Estimation, and Preparative Ultracentrifugation

Abstract: ClinicalTrials.gov Identifier: NCT01764633.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 17 publications
1
87
1
1
Order By: Relevance
“…As Friedewald equation is prone to underestimate LDL-C particularly in patients with very-low LDL-C, the FOURIER trial evaluating evolocumab in patients with known cardiovascular disease used preparative ultracentrifugation method for LDL-C estimation when Friedewald LDL-C was observed to be at 40 mg/dL 36) . Recently, Martin and colleagues have investigated the accuracy of LDL-C measurements in the FOURIER trial, specifically in PCSK9 inhibitor-treated patients achieving very-low LDL-C levels 40 mg/dL; their results showed that Martin method more closely resembled ultracentrifugation than the Friedewald approach, suggesting it should be the preferred method to estimate LDL-C levels in such intensively treated patients 38) . Our findings are in line with these results showing significant upward discordance using the two novel LDL-C equations compared to Friedewald estimates in similar patients at high cardiovascular risk and very-low LDL-C under 40 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…As Friedewald equation is prone to underestimate LDL-C particularly in patients with very-low LDL-C, the FOURIER trial evaluating evolocumab in patients with known cardiovascular disease used preparative ultracentrifugation method for LDL-C estimation when Friedewald LDL-C was observed to be at 40 mg/dL 36) . Recently, Martin and colleagues have investigated the accuracy of LDL-C measurements in the FOURIER trial, specifically in PCSK9 inhibitor-treated patients achieving very-low LDL-C levels 40 mg/dL; their results showed that Martin method more closely resembled ultracentrifugation than the Friedewald approach, suggesting it should be the preferred method to estimate LDL-C levels in such intensively treated patients 38) . Our findings are in line with these results showing significant upward discordance using the two novel LDL-C equations compared to Friedewald estimates in similar patients at high cardiovascular risk and very-low LDL-C under 40 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…The novel Martin-Hopkins formula improves the accuracy of cLDLC at various conditions including very low LDLC < 1.8 mmol/L and in nonfasting samples [47,48]. We recommend to use it preferably in the range of TG concentrations 2.0−4.5 mmol/L wherein the Friedewald equation is less accurate [47].…”
Section: Calculated Ldlcmentioning
confidence: 99%
“…12 A novel method of calculating LDL-C, the Martin-Hopkins equation, was developed in 2013 and uses an adjustable factor for the TG:VLDL-C ratio, which allows for more accurate estimation of LDL-C, particularly in setting of hypertriglyceridemia (150-399 mg/dL). 12,13 This equation compares favorably among men and women [mean age of 59 years (interquartile range [IQR]: 49-69)] against results derived using ultracentrifugation (correlation coefficient of 0.99; overall concordance in classification of LDL-C by guideline categories of 91.7%). 12,13 Mehta et al showed improved concordance with LDL-C and secondary measures of cardiovascular risk, specifically apoB and non-HDL-C, using Martin-Hopkins equation compared with the Friedewald equation.…”
mentioning
confidence: 99%
“…12,13 This equation compares favorably among men and women [mean age of 59 years (interquartile range [IQR]: 49-69)] against results derived using ultracentrifugation (correlation coefficient of 0.99; overall concordance in classification of LDL-C by guideline categories of 91.7%). 12,13 Mehta et al showed improved concordance with LDL-C and secondary measures of cardiovascular risk, specifically apoB and non-HDL-C, using Martin-Hopkins equation compared with the Friedewald equation. 14 Because hypertriglyceridemia is more common in HIVinfected versus HIV-uninfected people, 15 inaccuracy of cal-culated LDL-C using the Friedewald equation may be an important clinical issue for PWH.…”
mentioning
confidence: 99%